A statistical analysis of medium-scale traveling ionospheric disturbances during 2014–2017 using the Hong Kong CORS network - Guanyi Chen; Chen Zhou; Yi Liu; Jiaqi Zhao; Qiong Tang; Xiang Wang; Zhengyu Zhao (Earth, Planets and Space, 2019)
Abstract We report a statistical study of medium-scale traveling ionospheric disturbances (MSTIDs) during 2014–2017 in the low-latitude China region using the Hong Kong Continuously Operating Reference Stations network with a baseline length of 10–15 km. Polynomial fitting and the multichannel maximum entropy method are utilized to derive MSTID parameters from global positioning system total electron content data. We find that MSTIDs can be sorted into three types in this region. One type is daytime MSTIDs, which are mainly distributed during 1000–1700 local time (LT) in spring, autumn and winter. The second type is nighttime MSTIDs, which mainly occur from 2200 to 0300 LT in spring and summer. The third type is morning MSTIDs, mainly occurring from 0500 to 0700 LT in spring and autumn. No clear difference in the MSTID parameters is distinguishable between the cyclone period and non-cyclone period, which may be due to the distance restriction for cyclone identification and different propagation distances of the primary gravity waves (GWs) and secondary GWs.